Older Workers' Adjustments to Plant Closures - Mazerolle, Maurice J.; Singh, Gangaram (Relations industrielles / Industrial Relations, 1999)
This article investigates whether older workers affected by plant closures are more likely to be discouraged from participation in the labor force and to be bitter towards employers as well as whether they are less likely to report career growth in subsequent employment situations. The data indicated that older workers are less likely to report the career-growth effect. In addition, post-closure training activities reduced the likelihood of the discouraged-worker effect for the 45-55 age group. The respondents from the older age groups who undertook post-closure training activities were more likely to report the poisoning effect and less likely to report the career-growth effect. It is argued that the results relate to the definition of the age groups, the transferability of human capital, and the value of community support. The implication of the results for public and institutional policies are discussed.
Keywords: Age and employment; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Employee attitude; Employees; Labor Unions; Labor relations; Older workers; Plant closures; Psychology; Regression analysis; Shutdowns; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies